Relationship between Glycemic Control in Type II Diabetes Mellitus and Anaemia (Academia Journal of Medicine, 2019)
Background: Chronic hyperglycemia in uncontrolled diabetes is related to higher incidence of anaemia which goes unrecognized prior to the  development of chronic renal failure.This study was conducted to know the prevalence of Anaemia in persons with with Type II Diabetes  Mellitus,in relation to glycemic control using HbA1c as a tool to it. Subjects and Methods: 60 Diabetic subjects were divided into two  groups of 30 each based on their glycemic control(group A,with poor glycemic control and group B with good glycemic control taking 7%  Hba1c as cut off value),incidence of anaemia was measured and compared among them and also with 30 age and sex matched healthy non  Diabetic controls. Results: Incidence of anaemia was found to be significantly higher in diabetics group as compared to non diabetics and  among diabetics it was significantly higher in uncontrolled group as compared to group with controlled diabetes. Conclusion: Good glycemic  control in diabetes is associated with a better haemoglobin levels,hence it is desirable to evaluate the haemoglobin level often to monitor the  micro and macrovascular complications of diabetes even when the renal parameters are normal.
Keywords: Diabetes; Anaemia; Glycemic control; HbA1c; micro and macro vascular complications